The Epilogue in Doctor Faustus: The Petrarchan Context - Eriksen, Roy (Nordic Journal of English Studies, 2010)
Metaphors used in Epilogue in Doctor Faustus, particularly the cut branch and Apollo‟s burned laurel bough, are indicative of Marlowe‟s intellectual involvement with Petrarch and the former‟s role in the literary circle centered on the Countess of Pembroke. His Latin epistle to Mary Sidney in Thomas Watson‟s Amyntas (1592) repeats similar metaphors, and the combination in the Epilogue of these images with that of the “forward wits” point both to Petrarch‟s Sonnet 269 (“Rotta l‟alta colonna e ‟l verde lauro”) and Sonnet 307 (“I‟ pensava assai destro esser sul l‟ale”). In fact, lines in the Epilogue are strongly evocative of some verses in Sonnet 307, where Petrarch ponders the theme of overreaching. The Epilogue thus would document a continuation of the interest in Petrarch that is so evident in the Tamburlaine plays.